Health and Tourism: Implications of COVID-19 Pandemic to the Malaysian Travel and Hospitality Industry - Norhanim Abdul Razak (International Journal of Supply Chain Management, 2020)
Outbreaks of diseases which are contagious and can pose serious health consequences have considerable impacts on the tourism and hospitality industry. This is reflected through past outbreaks such as foot and mouth disease (FMD), SARS, Ebola and Chikungunya. Due to the importance of health in the context of tourism, it is imperative to investigate the extent of the impact of COVID-19 health pandemic as it is considered one of the worst disease outbreaks globally. Thus, this paper aims to explore the implications of Coronavirus (COVID-19) on Malaysian tourism and hospitality industry. After content analysing 63 newspaper articles published online from March to May 2020, it is uncovered that the Malaysian tourism and hospitality industry has been affected terribly by the enforcement of MCO in order to curb the spread of COVID-19 health pandemic. Stories associated with income and job losses, cancellation of Visit Malaysia 2020 campaign, closure of tourist attractions and closing down of countless of hotels were apparent in the reporting of online news. Yet, the analysis of this paper adds to the existing knowledge by revealing that despite encountering difficulty during this time of crisis, the Malaysian hospitality industry was able to show their appreciation towards medical frontliners who risk their lives to save COVID-19 patients. Some hotels demonstrate their corporate social responsibility (CSR) by offering free accommodation and other services to health personnel.